Impact of the radiation effect on the energy storage density and wake-up behaviors of antiferroelectric-like Al-doped HfO2 thin films. Issue 38 (24th September 2020) - Zhang, W. L.; Mao, Y. H.; Cui, L.; Tang, M. H.; Su, P. Y.; Long, X. J.; Xiao, Y. G.; Yan, S. A.
Abstract : The effect of the γ-ray total dose radiation on the energy storage density (ESD) and the phase transition of antiferroelectric-like (AFE-like) Al-doped HfO2 (HfAlO) thin films was investigated. Abstract : The effect of the γ-ray total dose radiation on the energy storage density (ESD) and the phase transition of antiferroelectric-like (AFE-like) Al-doped HfO2 (HfAlO) thin films was investigated. The ESD property and wake-up behavior of the phase transition during the field cycling of the AFE-like HfAlO thin films were quantified before and after the radiation. The efficiency of the AFE-like thin films for energy storage slightly decreases as the total dose increases from 200 krad (Si) to 5 Mrad (Si), which is attributed to the radiation-induced trapped defects at the interfaces of HfAlO/TiN. Both the J – E, C – V, and ε r – f characteristics of the AFE-like HfAlO thin films were also measured before and after the radiation at the same electrodes. These results further confirm that the ferroelectricity of the thin films can be reduced due to the radiation oxide trapped defects. It is worth noting that an enhanced wake-up behavior of the AFE-like HfAlO thin films can be observed after the radiation, which indicates that the transition from the antiferroelectric phase to the ferroelectric phase could be accelerated by the increased radiation-induced defects.